Land Reform dalam Kebijakan Politik Hukum Pertanahan - Zumiyati S. Ibrahim (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2020)
The concept of agrarian renewal has been much acclaimed and one concept that until now has not been completed in its implementation and even seems abandoned is the land policy known as